2022
DOI: 10.1038/s41419-022-04788-8
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β induces GBM mesenchymal transition through upregulation of CLDN4 and nuclear translocation to activate TNF-α/NF-κB signal pathway

Abstract: Glioblastoma (GBM) is the most common and aggressive primary malignant brain tumor. The unregulated expression of Claudin-4 (CLDN4) plays an important role in tumor progression. However, the biological role of CLDN4 in GBM is still unknown. This study aimed to determine whether CLDN4 mediates glioma malignant progression, if so, it would further explore the molecular mechanisms of carcinogenesis. Our results revealed that CLDN4 was significantly upregulated in glioma specimens and cells. The inhibition of CLND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 74 publications
(39 reference statements)
2
29
0
Order By: Relevance
“…RREB1 has been observed to act as an essential partner in the induction of EMT by the TGF-β1 pathway in tumors [30]. Increasing evidences show that TGF-β1 pathway was activated to promote the biological progression of glioma [47,48]. We further explored the correlation between RREB1 and TGF-β1 signaling pathway related signatures, and confirmed that the HALLMARK_TGF_BETA_SIGNALING signature enriched in higher RREB1 group.…”
Section: Discussionsupporting
confidence: 59%
“…RREB1 has been observed to act as an essential partner in the induction of EMT by the TGF-β1 pathway in tumors [30]. Increasing evidences show that TGF-β1 pathway was activated to promote the biological progression of glioma [47,48]. We further explored the correlation between RREB1 and TGF-β1 signaling pathway related signatures, and confirmed that the HALLMARK_TGF_BETA_SIGNALING signature enriched in higher RREB1 group.…”
Section: Discussionsupporting
confidence: 59%
“…For instance, IL-17 promotes tumorigenesis by regulating beclin-1 ubiquitination [ 27 ]. The TNF signaling pathway mediates the mesenchymal transition of glioblastoma and plays a key role in its progression [ 28 ]. The data showed that several signaling pathways with different functions might be involved in the occurrence and development of nicotine-related oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, coupled with modeling intercellular crosstalk by NicheNet method, we investigated potential ligand-receptor-target interactions between tumor and non-tumor cells. Our unbiased analysis uncovered some interesting ligands, such as TGFB1, a master inducer in the mesenchymal transition, 59,60 which can promote the majority of our curative targets. LGALS3, produced by a variety of different cells, including macrophages, and endothelial cells, acts as another major source of this transcriptome change.…”
Section: Discussionmentioning
confidence: 99%